1998
DOI: 10.1046/j.1365-2109.1998.00885.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the beta-agonist ractopamine on growth hormone and intermediary metabolite concentrations in rainbow trout, Oncorhynchus mykiss (Walbaum)

Abstract: Rainbow trout, Oncorhynchus mykiss (Walbaum), with a mean initial weight of 196 g were fed the β-agonist ractopamine incorporated into a commercial rainbow trout diet at 0, 5, 10, 20 or 40 p.p.m. for 12 weeks. The experiment was conducted as a completely randomized design, with five treatments and four replicate tanks. At the start of the trial and every 4 weeks subsequently, fish were euthanized, and blood serum and liver samples were collected. Serum glucose concentrations were significantly higher in fish f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The overall finding of these researchers indicated that β‐AR agonists influence growth and body composition, mainly reducing fat and increasing protein content in muscle. Dietary administration of ractopamine to rainbow trout also moderately altered the concentration of circulating GH, glucose and NEFA (Van den Berg et al . 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The overall finding of these researchers indicated that β‐AR agonists influence growth and body composition, mainly reducing fat and increasing protein content in muscle. Dietary administration of ractopamine to rainbow trout also moderately altered the concentration of circulating GH, glucose and NEFA (Van den Berg et al . 1998).…”
Section: Introductionmentioning
confidence: 99%
“…(1998) found increased amino acid uptake into cattle muscle using the closed hind limb perfusion model, but the rainbow trout diet used in the present study contained >40% protein, so changes in either plasma protein or amino acids by enhanced uptake seem unlikely, although this needs to be established. The study by Vandenberg et al . (1998) reported significantly elevated plasma glucose concentrations only after 12 weeks, but not before, when rainbow trout were fed RACT.…”
Section: Discussionmentioning
confidence: 94%
“…The anabolic effects of β 2 ‐AAs have been reported for many mammalian species (including rodents, ruminants and pigs), avian species (chickens, turkeys and ducks) and three teleost species [channel catfish Ictalurus punctatus (Rafinesque), Mustin & Lovell, 1993; blue catfish Ictalurus furcatus (Valenciennes), Webster et al ., 1995; rainbow trout, Vandenberg & Moccia, 1998; Vandenberg et al ., 1998]. In general, substantially larger anabolic responses are obtained in rodents and ruminants, with average responses in pigs, turkeys and ducks and lower responses in chickens (Beermann, 1993; Mersmann, 1998; Moody et al ., 2000) and more modest responses in fishes (Mustin & Lovell, 1993; Vandenberg & Moccia, 1998; Vandenberg et al ., 1998). Comparisons across studies are difficult due to differences in the agonist studied, dosage, duration and especially response variables measured so this discussion will be restricted specifically to the β 2 ‐AAs CLEN and RACT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules have been widely studied and used in the treatment of chronic airway diseases such as bronchial asthma (Nabil, Elessawy, Hosny, & Ramadan, 2014;Ura, Tanaka, Takahashi, Yamazaki, & Fujimoto, 2016). On the other hand, β-agonists are often illegally added into the feed of food animals to increase the lean meat (Karamolegou, Dasenaki, Belessi, Georgakilas, & Thomaidis, 2018;Li et al, 2018) and to confer advantages such as increased feed efficiency and decreased time to market (Vandenberg, Leatherland, & Moccia, 2015). However, these drugs may remain in the edible parts of those animals, and their residues may threaten human health.…”
Section: Introductionmentioning
confidence: 99%